2017
DOI: 10.5812/ijem.57927
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ginger on Fasting Blood Sugar, Hemoglobin A1c, and Lipid Profiles in Patients with Type 2 Diabetes

Abstract: BackgroundLipid and glycemic abnormalities are prevalent in diabetes leading to long term complications. Use of safe and natural foods instead of medications is now considered by many scientists.ObjectivesThis study aimed at determining the effect of ginger on lipid and glucose levels of patients with type 2 diabetes mellitus.MethodsIn a double‐blind placebo-controlled trial, 50 patients with type 2 diabetes were randomly allocated to 2 groups of intervention (n = 25) and placebo (n = 25). Each patient receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
0
28
0
1
Order By: Relevance
“…For instance, ginger supplementation has been found to notably reduce fasting blood sugar, HbA1c, and insulin resistance [85][86][87]. Additionally, lipid profiles (e.g., total cholesterol, and LDL-C), C-reactive protein, obesity-related cardiovascular risk factors have been found to reduce with ginger intake [24,[88][89][90]. In general, ginger has been found to indicate a beneficial effect on high dosage and long-term treatment in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ginger supplementation has been found to notably reduce fasting blood sugar, HbA1c, and insulin resistance [85][86][87]. Additionally, lipid profiles (e.g., total cholesterol, and LDL-C), C-reactive protein, obesity-related cardiovascular risk factors have been found to reduce with ginger intake [24,[88][89][90]. In general, ginger has been found to indicate a beneficial effect on high dosage and long-term treatment in metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Black et al (2009) [47] Arm muscle pain intensity muscle soreness (mm)24-post, range of motion, Arm volume, Isometric force, ROM (mean percent change in range of motion, %), Volume (percent change in arm volume, %), Force (percent change in isometric force, %), PGE2 (pg/mL), and ratings of perceived exertion Taking raw and heat-treated ginger helped to reduce muscle pain following exercise-induced muscle injury. No Mahluji et al (2013) [48] Serum FBG, HbA1c, insulin, HOMA, QUICKI, TG, TC, LDL-C, HDL-C Ginger supplementation had a significant effect in reducing the levels of insulin, LDL-C, TG, and HOMA, and it increased the QUICKI index compared to the control group.…”
mentioning
confidence: 99%
“…It is highlighted that medication adherence remained higher in individuals in the EG, in both tests, although without statistical significance. A number of research studies that investigated the effect of ginger in the treatment of T2DM, in different doses and intervention periods, also showed reduced FBS and TC values ( 9 , 11 , 22 - 23 ) .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the worldwide interest in research involving the use of alternative and complementary practices has been increasing. This interest is due to factors such as the search for affinities for the use of natural products; the high price of private medical assistance, together with the high cost of the medications; precarious public assistance; and the attempt to mitigate complications related to chronic diseases, such as T2DM ( 5 - 9 ) . In this sense, ginger appears as a promising adjuvant for the treatment of T2DM, mainly acting in the regulation of lipid metabolism, in the improvement of anti-inflammatory activities, and in the modulation of insulin release and response, with minimal adverse events and increasingly effective results ( 10 - 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…A randomised placebo‐controlled trial showed that daily consumption of fresh ginger at ~1,000 mg significantly reduced serum fasting glucose by approximately ~20% in peritoneal dialysis patients (Imani et al, ). Another randomised controlled trial on patients with type 2 diabetes revealed that ginger administration at ~2,000 mg/d, for 10 weeks, significantly decreased fasting blood glucose and haemoglobin A1C (Makhdoomi Arzati et al, ). In addition, diabetic rats orally supplemented with aqueous ginger extract at 500 mg kg −1 day −1 had lower haemoglobin A1C compared with the control (Arikawe, Oyerinde, Olatunji, & Obika, ).…”
Section: Mechanistic Studiesmentioning
confidence: 99%